The Impact of Dividend Policy on Shareholders’ Wealth before and After Financial Melt down: Evidence from FMCG Sector in India - GejaLakshmi, Sandanam; Azhagaiah, Ramachandran (Financial Risk and Management Reviews, 2015)
Dividend policy (DP) of corporate sector is widely researched topic in finance however; it remains a debatable issue to decide what factors determine the DP. The objective of this paper is to analyze the impact of dividend policy (DP) on shareholders’ wealth (SW) of Fast Moving Consumer Goods (FMCG) sector in India. Out of 16 firms listed on National Stock Exchange (NSE) 13 firms that have been paying dividend consecutively for the past ten years are considered for analysis. In the light of the prior literature, key predictor variables such as earnings per share (EPS), dividends per share (DPS), retained earnings per share (RPS), price earnings ratio (PER), lagged price earning (LAGPER), earnings (EAR), and lagged market value (LAGMPS) are considered for analyzing the impact of DP on SW. The descriptive statistics reveals that the data form in to normal. Whereas when the assumptions needed to be fulfilled for the Ordinary Least Square method (OLS), the data are found to be homoskedastic and are free of autocorrelation. Augmented Dickey Fuller Test (ADF), White - Heteroskedasticity Test, Auto Correlation, Breuch-Godfrey Serial correlation LM test, Durbin-Watson, Lagrange Multiplier (LM) for Autoregressive conditional heteroskedasticity (ARCH-LM), Correlation, Ordinary Least Square Regression and Chow test are applied using Eviews 7 Econometrics software package for analysis. Regression result proves that DPS (121.65) and RPS (9.68) have significant positive co-efficient on EPS(SW) of FMCG firms in India before global financial melt down, while DPS (76.74), LAGPER (1.52) and LAGMPS (0.27) have significant positive co-efficient (76.74) on EPS(SW) of FMCG firms in India after global financial melt down. The results of the Chow test proves that the FMCG firms have significant shift-in-structure (positive improvement) in respect of SW after global financial melt down.